Endobronchial Tuberculosis Masquerading as a Lung Mass: A Rare and Challenging Diagnosis - I Gusti Ngurah Purwa Wedadinanta; Putu Dyah Widyaningsih; I Komang Rusgi Yandi (Jurnal Respirasi, 2026)
Introduction: Endobronchial tuberculosis (EBTB) is a rare form of tracheobronchial infection by Mycobacterium tuberculosis (MTB). It is estimated to occur in 10-40% of patients with active pulmonary TB. It often presents atypically and mimics other diseases, particularly in asymptomatic individuals. Case: We report a 25-year-old immunocompetent male with no respiratory symptoms or TB risk factors, who was incidentally found to have a pulmonary mass during routine chest X-ray screening. Physical and laboratory examinations were unremarkable. Chest computed tomography (CT) scan with contrast revealed an intensely contrast-enhancing solid mass in the posterior segment of the left lower lobe. Bronchoscopy showed partial obstruction of the left lower lobe bronchus with hyperemic, friable mucosa. Histopathology confirmed caseating granulomatous inflammation, establishing the diagnosis of EBTB. The patient was classified as having single-level EBTB and was treated with standard anti-TB therapy, without corticosteroids. Conclusion: This case highlights the diagnostic challenge of EBTB in individuals without typical symptoms or exposure history. Endobronchial TB presents a diagnostic challenge due to its variable and non-distinct clinical manifestations. Environmental exposure in TB-endemic regions, such as Indonesia, may play a role. The absence of molecular testing (e.g., tissue GeneXpert) is a limitation, though early histological diagnosis enabled timely management. Endobronchial TB should be considered in asymptomatic pulmonary lesions, particularly in endemic regions. Bronchoscopy and biopsy remain key to early detection of the disease.